A water molecule in the interior of a 1H-pyrazole Cu2+ metallocage. (25th April 2016) - Pitarch-Jarque, Javier; Belda, Raquel; Blasco, Salvador; Navarro, Pilar; Tejero, Roberto; Junquera-Hernández, José Miguel; Pérez-Mondéjar, Vicente; García-España, Enrique
Abstract : A pyrazole aza-macrocyclic Cu 2+ metallocage shows the inclusion of a water molecule not hydrogen bonded with any acceptor or donor groups of the cage. Abstract : Water has a great tendency to associate through hydrogen bonding with water molecules or other hydrogen bond donor or acceptor groups. Here the case of a water molecule encapsulated in the interior of a metallocage receptor is presented. The association of four copper(ii ) ions and two aza-macrocyclic receptors in which two 1 H -pyrazole units are connected by cadaverine diamines leads to the inclusion of a water molecule into the cage, as proved by X-ray analysis and infrared spectroscopy. The included water molecule shows no hydrogen bonding with any component of the cage presenting only a weak hydrogen bond with an oxygen atom of a perchlorate counter-anion. The IR stretching vibrations predicted by DFT calculations agree with the experimental results.